المسؤولية الجزائية لمدير شركة الشخص الواحد في النظام السعودي والقانون الأردني: The criminal responsibility of the director of a one-person company in the Saudi system and Jordanian law - Ayed Saad Ayed Alahmary,; Muhammad Abdurrahman Sadique , (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تهدف هذه الدراسة إلى دراسة طبيعة المسؤولية الجزائية لمدير شركة الشخص الواحد في النظام السعودي والقانون الأردني، وذلك من خلال الأساس القانوني للمسؤولية الجزائية لمدير شركة الشخص الواحد والذي يتمثل في الحرية والاختيار، ثم بيان شروط المسؤولية الجزائية لمدير شركة الشخص الواحد، ثم دراسة أركان المسؤولية الجزائية.كما تناول البحث أهم الحالات التي تنشأ فيها المسؤولية الجزائية لمدير شركة الشخص الواحد، ومدى الفارق بين النظام السعودي والقانون الأردني حيث اشتمل النظام السعودي على كثير من الحالات التي لم نجد لها نصا مشابها في القانون الأردني، فضلًا عن شدة العقوبات الواردة في النظام السعودي. وقد استخدم الباحث في هذه الدراسة المنهج التحليلي والمنهج والاستنباطي والمنهج المقارن، ومن خلال ذلك توصل الباحث إلى عدة نتائج: ومن أهمها أن المنظم السعودي لم يفرد تنظيما قانونيا خاصا بشركة الشخص الواحد كبقية الشركات التجارية، وتوصل أيضاً إلى أن أساس المسؤولية الجزائية هي وجود الضرر كذلك بأن آثار المسؤولية الجزائية ضد مدير شركة الشخص الواحد هي تعويض الضرر الناتج عن الإخلال بالتزام مقرر في ذمته. الكلمات المفتاحية: المسؤولية، الجزائية، شركة الشخص الواحد. Abstract This study aims to study the nature of the criminal liability of one-person company director in both the Saudi and Jordanian systems in light of the legal basis of the criminal liability of one-person company director which is represented in freedom and choice. It also aims to present the conditions for criminal liability of one-person company director, and to examine the pillars of criminal liability. Additionally, it aims to highlight the most important situations in which the criminal liability apply to one person company director; and the difference between the Saudi system and the Jordanian system as the Saudi law contains several provisions for situations which the Jordanian law does not have, besides the severity of penalties in the Saudi law. The researcher used the analytical, inductive, and comparative methods by which several findings were achieved. The most important of which are the Saudi government did not create any exclusive legal regulations for one-person companies as it is the case for other companies. Also, the basis of criminal liability is the existence of harm, and the effects of criminal liability of one-person company director requires him to compensate for the damage caused by the breach of his obligations. Keywords: the responsibility, penal, one-person company